Adding LIT to HIIT - is low-intensity training vital for endurance-trained athletes during a 7-day HIIT shock microcycles? - Strepp, T.; Blumkaitis, J. C.; Haller, N.; Stöggl, T. L. (Medicine & Science in Sports & Exercise, 2024)
Purpose To investigate the effects of a 7-day high-intensity interval training shock microcycle (HIIT-SM) with or without additional low-intensity training (LIT) on aerobic fitness and endurance performance compared to a control group.